In vivo Emergence of Colistin and Tigecycline Resistance in Carbapenem-Resistant Hypervirulent Klebsiella pneumoniae During Antibiotics Treatment - Chen, Jiawei; Zeng, Yu; Zhang, Rong; Cai, Jiachang (Frontiers in Microbiology, 2021)
Three carbapenem-resistant Klebsiella pneumoniae (CRKP; strains KP-426, KP-C76, and KP-CT77) were isolated from a patient with severe burns during the treatment of colistin and tigecycline. Single-nucleotide polymorphism typing showed that three ST11 CRKP were clonally related. Three isolates harbored the same set of antimicrobial resistance genes. blaKPC-2, blaSHV-12, blaTEM-1, and rmtB genes were located on the same 128,928-bp IncFII/IncR plasmid. Tet(A), catA2, sul2, and dfrA14 genes were located on a plasmid with an unknown Inc-type. blaSHV-11, fosA, and aadA2 were chromosomal genes. An IS1 and an ISKpn14 were found in the promoter region of the mgrB gene of two colistin-resistant CRKP, K. pneumoniae KP-C76, and KP-CT77, respectively. A novel amino acid substitution, G300E, was identified in the type 1 Tet(A) variant of K. pneumoniae KP-CT77 which exhibited high-level tigecycline resistance compared to strains KP-426 and KP-C76 (MIC of 32, 4, and 4mg/l, respectively). Conjugation and cloning experiments confirmed that the mutated Tet(A) resulted in a 4-fold increase in tigecycline minimal inhibitory concentration (MIC) of Escherichia coli. Three CRKP belonged to the K64 serotype and possessed a similar IncHI1B/repB virulence plasmid carrying rmpA, rmpA2, and iucABCDiutA. The survival rates of Galleria Mellonella injected with K. pneumoniae KP-426, KP-C76, and KP-CT77 were 4.2, 20.8, and 8.3%, respectively. The emergence of colistin and tigecycline resistance in carbapenem-resistant hypervirulent K. pneumoniae posed a serious threat to clinical anti-infective therapy. The type 1 Tet(A) variant carrying G300E mutation, which conferred significantly elevated tigecycline MIC and was located on a conjugative plasmid, needs attention.